Militarization in Childhood Education: A Critical Examination of the Semi-Military Schooling Model in West Java - Syarifah, Hannik Naylatus; Musrifah; Rifan, Ahmad Arif (Education : Jurnal Sosial Humaniora dan Pendidikan, 2025)
Education is ideally a space for shaping character, promoting equality, critical awareness, and freedom of thought. However, in practice, there is a growing tendency toward militaristic approaches, particularly within institutions that adopt semi-military systems. This model emphasizes strict discipline, hierarchy, and absolute obedience, which ultimately suppresses learners' autonomy, creativity, and critical thinking. Such an approach contradicts the principles of critical pedagogy, which prioritize dialogue, participation, and liberation within the learning process. This study employs a qualitative approach with a critical case study design to explore and analyze the phenomenon of militaristic education within formal educational institutions in Indonesia. Data were collected through a literature review involving academic journals, policy reports, and institutional documentation. The data were analyzed descriptively and critically to examine the tension between authoritarian educational practices and the ideals of critical pedagogy. The findings highlight the urgent need to shift from repressive and hierarchical educational models to more humanistic, participatory, and emancipatory approaches. An education system that upholds human values is expected to foster democratic learning environments and empower students to become reflective individuals and active agents of social transformation.